Parton shower contributions to jets from high rapidities at the LHC - Deák, M; Hautmann, F; Jung, H; Kutak, K (2012)
We discuss current issues associated with the dependence of jet distributions at the LHC on the behavior of QCD parton showers for high rapidities.